2022
DOI: 10.1093/femsre/fuac042
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models of COVID-19

Abstract: Although COVID-19 has only recently appeared, research studies have already developed and implemented many animal models for deciphering the secrets of the disease and provided insights into the biology of SARS-CoV-2. However, there are several major factors that complicate the study of this virus in model organisms, such as the poor infectivity of clinical isolates of SARS-CoV-2 in some model species, and the absence of a persistent infection, immunopathology, severe acute respiratory distress syndrome, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 225 publications
0
4
0
Order By: Relevance
“…Zebrafish have also been effectively utilized to model neurodegenerative diseases [56], behavioral disorders [57,58], neuromuscular disorders [59][60][61][62][63], aging-related disorders [64][65][66], hematopoietic disorders [67][68][69][70], renal diseases [71][72][73][74], liver diseases [74][75][76][77], and eye diseases [78][79][80][81], to mention a few. In recent years, zebrafish have also been used to study infectious viral diseases, such as Zika [82] and COVID-19 [83].…”
Section: Zebrafish Models For Human Disordersmentioning
confidence: 99%
“…Zebrafish have also been effectively utilized to model neurodegenerative diseases [56], behavioral disorders [57,58], neuromuscular disorders [59][60][61][62][63], aging-related disorders [64][65][66], hematopoietic disorders [67][68][69][70], renal diseases [71][72][73][74], liver diseases [74][75][76][77], and eye diseases [78][79][80][81], to mention a few. In recent years, zebrafish have also been used to study infectious viral diseases, such as Zika [82] and COVID-19 [83].…”
Section: Zebrafish Models For Human Disordersmentioning
confidence: 99%
“…Zebrafish has also been demonstrated to be a reliable model system for studying human viral pathologies, including the most recent coronavirus disease 2019 [13]. For 2 of 20 example, using an adult zebrafish model, it was observed that intranasally delivered SARS-CoV-2 S spike protein caused severe olfactory histopathology, providing key insights for the evaluation of the mechanisms of action and side effects of human intranasally delivered vaccines against SARS-CoV-2 [14].…”
Section: Zebrafish As Inflammation Modelmentioning
confidence: 99%
“…For instance, zebrafish models of severe acute respiratory syndrome coronavirus 2, using an injection of the virus or viral antigens, have been developed that. These models are invaluable for studying host immune responses, vaccine mechanisms, potential side effects, and increased susceptibility of the elderly to COVID-19 infection [49]. Furthermore, zebrafish-based research on non-pathogenic microorganisms, such as gut microbiome, is flourishing [50].…”
Section: Expanding Applications Of Zebrafish In Biologymentioning
confidence: 99%